PERSEPSI GURU SMP ISLAM TERPADU ALFITYAH TERHADAP PEMBINAAN PRESTASI OLAHRAGA FUTSAL - Nabil Ibadurrahman; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Achievement building at Alfityah Integrated Islamic Junior High School needs to be done to make the alumni trained and experienced since junior high school, when these students are directed to enter the same high school, then they get an easy way to directly excel at the high school level, by making a path to reach their dreams and dreams. Their goal of having a career in futsal is even becoming a national team player. The purpose of this study was to determine the perceptions of Alfityah Integrated Islamic Junior High School teachers towards achievement coaching, so that the coach can understand where the shortcomings and mistakes are in the development of futsal sports achievement, so that in the future it can improve school performance in the futsal sport. This research took place at the Alfityah Integrated Islamic Junior High School, Jl Swakarya Ujung, Tuah Karya, Kec. Handsome, Pekanbaru City was held in July 2019 - July 2020, the entire population was sampled (total sampling) of 18 people. Based on the descriptions of the research results, it can be seen that the Perceptions of Alfityah Integrated Islamic Junior High School Teachers on Futsal Sports Achievement Development consist of external and internal factors. On external factors, results show that as many as 0 teachers (0%) stated very high, 4 teachers (40%) stated high, 4 teachers (40%) stated moderate, 1 teacher (10%) stated low, and 1 teacher (10%) stated very low. So it can be seen that the teacher's perception of external factors is in the high category. On internal factors, the results show that 1 teacher (10%) stated very high, 1 teacher (10%) stated high, 4 teachers (40%) stated moderate, 4 teachers (40%) stated low, and 0 teachers (0%) stated that it is very low. So it can be seen that the teacher's perception of internal factors is in the low category. Based on the calculation of the overall data, it can be read that 1 teacher (10%) stated very high, 2 teachers (20%) stated high, 3 teachers (30%) stated moderate, 4 teachers (40%) stated low, and 0 teachers ( 0%) stated very low. It can be seen that the Perception of Alfityah Integrated Islamic Junior High School Teachers towards Futsal Sports Achievement Development is in the low category with a percentage of 40%.Key Words: Teacher Perception, Futsal Sports Achievement Development